MR elastography in a murine stroke model reveals correlation of macroscopic viscoelastic properties of the brain with neuronal density - Freimann, Florian Baptist; Mueller, Susanne; Streitberger, Kaspar-Josche; Rot, Sergej; Ghori, Adnan; Vajkoczy, Peter; Reiter, Rolf; Braun, Juergen; Sack, Ingolf; Guo, Jing (NMR in Biomedicine, 2013)
The aim of this study was to investigate the influence of neuronal density on viscoelastic parameters of living brain tissue after ischemic infarction in the mouse using MR elastography (MRE). Transient middle cerebral artery occlusion (MCAO) in the left hemisphere was induced in 20 mice. In vivo 7-T MRE at a vibration frequency of 900 Hz was performed on days 3, 7, 14 and 28 (n=5 per group) after MCAO, followed by the analysis of histological markers, such as neuron counts (NeuN). MCAO led to a significant reduction in the storage modulus in the left hemisphere relative to contralateral values (p=0.03) without changes over time. A correlation between storage modulus and NeuN in both hemispheres was observed, with correlation coefficients of R=0.648 (p=0.002, left) and R=0.622 (p=0.003, right). The loss modulus was less sensitive to MCAO, but correlated with NeuN in the left hemisphere (R=0.764, p=0.0001). In agreement with the literature, these results suggest that the shear modulus in the brain is reduced after transient ischemic insult. Furthermore, our study provides evidence that the in vivo shear modulus of brain tissue correlates with neuronal density. In diagnostic applications, MRE may thus have diagnostic potential as a tool for image-based quantification of neurodegenerative processes. © 2013 John Wiley & Sons, Ltd.
CRIS-Team Scopus Importer:2022-08-03
Keywords: Ischemia; Middle cerebral artery occlusion; Mouse brain; MR elastography; Neuronal density; Stroke; Viscoelastic network